Expanded guarantees for banks Benefits, costs and exit issues - Schich, Sebastian (OECD Publishing, 2010)
This article argues that the expansion of existing and the introduction of new guarantees for financial institutions has been a key element of the policy response to the recent financial crisis. Essentially, the government expanded its role as the provider of the safety net for banks by adopting the function of a guarantor of last resort. Among the various policy response measures, the expansion of guarantees has the benefit of entailing lower upfront fiscal costs relative to other options. Guarantees are not without cost however. Even if they do not generate significant upfront fiscal costs, they create contingent fiscal liabilities. Other potential costs include those arising from distortions to competition and incentives (moral hazard). For example, there may be a perception that similar guarantees will always be made available at low costs. The fact that the expansion of guarantees has not been as closely co-ordinated across borders as might have been desired has resulted in additional costs. To avoid additional costs arising from inconsistencies in exit strategies, close communication and coordination regarding pricing and timing issues is required, especially as a more formal framework for the public provision of insurance would still need to be developed
Keywords: Finance and Investment